2010
DOI: 10.1108/09604521011011603
|View full text |Cite
|
Sign up to set email alerts
|

Consumer trust in service companies: a multiple mediating analysis

Abstract: Purpose -The concept of "trust" has gained considerable importance in the field of marketing during the last decades and is seen as a key mediator of customer relationship marketing. But upon a closer look at the literature, the construct "trust" is conceptualized and measured very differently. Based on a literature review and theoretical work, the purpose of this paper is to develop a conceptual model of consumer trust in a service company, which distinguishes two fundamental dimensions. Using these dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
162
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(180 citation statements)
references
References 62 publications
(86 reference statements)
15
162
0
3
Order By: Relevance
“…H4: Satisfaction positively influences Trust (β 12 =0.31; p<0.005). This finding supports the previous research on the mediating role that satisfaction plays in the Service Quality -Trust relationship conducted by Fullerton and Taylor (2002);and Kantsperger and Kunz, (2010). H5: Satisfaction positively influences Loyalty (β 13 =0.66; p<0.001), complying with the results of many other studies (e.g., Allen, 2004;Walsh et al, 2008;Torres-Moraga et al, 2008).…”
Section: Hypotheses Testing Resultssupporting
confidence: 81%
“…H4: Satisfaction positively influences Trust (β 12 =0.31; p<0.005). This finding supports the previous research on the mediating role that satisfaction plays in the Service Quality -Trust relationship conducted by Fullerton and Taylor (2002);and Kantsperger and Kunz, (2010). H5: Satisfaction positively influences Loyalty (β 13 =0.66; p<0.001), complying with the results of many other studies (e.g., Allen, 2004;Walsh et al, 2008;Torres-Moraga et al, 2008).…”
Section: Hypotheses Testing Resultssupporting
confidence: 81%
“…Initial results have shown that the good quality and consistent service will create trust among customers (Hazra, Kailash, & Srivastava, 2009;Kantsperger & Kunz, 2010). In addition, the trust is able to maintain a good long-term relationship between organizations and customers (Garbarino & Johnson, 1999;Morgan & Hunt, 1994).…”
Section: Service Quality and Trust In Zakat Institutionsmentioning
confidence: 99%
“…One of the reasons that contribute to this phenomenon is the low on trust in zakat institutions. The trust issues arise due to several things like inefficient distribution of zakat, zakat fund surplus that has not been distributed to eligible recipients, tarnished reputation and low quality of service (Abratt & Kleyn, 2012;Hairunnizam et al, 2010;Kantsperger & Kunz, 2010;Nur Hafizah & Selamah, 2013;Sanep & Hairunnizam, 2005b).…”
Section: Trust In Zakat Institutionsmentioning
confidence: 99%
“…problem solving and development of analytical capabilities, among undergraduate students in real life contexts (Bonnet et al 2006, Ehab and Lashine 2003, Jones 2007. While education can be viewed as service (Lovelock 1983), especially in a UI-collaboration context and trust is of importance in service industries (Kantsperger and Kunz 2010,) it is of interest exploring t the role of trust in an education context. Dagger & O'Brian (2010) has in their studies regarding consumers experience found indications on how trust varies as a function of customers experience in a relationship.…”
Section: Introductionmentioning
confidence: 99%